PENGARUH DEBT RATIO TERHADAP LIKUIDITAS (Studi pada PT Tambang Bukit Asam, Tbk Periode 2010 - 2017) - Ryando, Ryando (JURNAL ILMIAH M-PROGRESS, 2021)
The purpose of this study is to determine the development of liquidity which is proxied by the Current Ratio and Debt Ratio which is proxied by the Debt to Equity Ratio at PT. Bukit Asam Tbk. The writing method used is the quantitative writing method, meaning research that describes or tells and describes how the results of the calculation of the company's financial data in the form of financial statements. The object of the research is PT. Bukit Asam Mine, Tbk. The primary data used is the Financial Report in the form of a balance sheet and income statement for the 2010-2017 period. The data analysis method uses classical assumption test analysis, multiple correlations, multiple regression, coefficient of determination, and hypothesis testing. The results of the Debt to Equity Ratio research have a regression coefficient of -7.011 and a significant level of 0.004. This means that H1 is accepted so that it can be said that the Debt to Equity Ratio has a negative and significant effect on liquidity which is proxied by the Current Ratio. Based on the results of the study, the F value was 0.2047 or 20.47% with a significance level of 0.004. Because the significance level is less than 0.05, it can be said that the H1 hypothesis is accepted, namely, debt to equity has a negative and significant effect on the current ratio.Â Kata Kunci: CR dan DER